2008
DOI: 10.1038/mt.2008.44
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Molecular Targetingof 15-Lipoxygenase-1 in Colon Cancer

Abstract: Molecular targeting for apoptosis induction is being developed for better treatment of cancer. Downregulation of 15-lipoxygenase-1 (15-LOX-1) is linked to colorectal tumorigenesis. Re-expression of 15-LOX-1 in cancer cells by pharmaceutical agents induces apoptosis. Antitumorigenic agents can also induce apoptosis via other molecular targets. Whether restoring 15-LOX-1 expression in cancer cells is therapeutically sufficient to inhibit colonic tumorigenesis remains unknown. We tested this question using an ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…15-LOX-2 was undetected in both adenomas and normal tissue [36] . Apart from this, in vivo studies from Nixon et al [24] and Wu et al [26] , and evidence of transcriptional silencing of 15-LOX-1 in cancer cells in a different study [35] strengthened the anti-carcinogenic role of 15-LOX-1. Yuri et al [38] have reported down-regulation of 15-LOX-1 in colorectal adenomas.…”
Section: Anti-carcinogenic Roles Of 15-lox-1 In Colon Cancermentioning
confidence: 95%
See 4 more Smart Citations
“…15-LOX-2 was undetected in both adenomas and normal tissue [36] . Apart from this, in vivo studies from Nixon et al [24] and Wu et al [26] , and evidence of transcriptional silencing of 15-LOX-1 in cancer cells in a different study [35] strengthened the anti-carcinogenic role of 15-LOX-1. Yuri et al [38] have reported down-regulation of 15-LOX-1 in colorectal adenomas.…”
Section: Anti-carcinogenic Roles Of 15-lox-1 In Colon Cancermentioning
confidence: 95%
“…Although several inter-conflicting reports have been published, convincing recent evidences from several in vitro and in vivo studies, especially the ones in the latter category from Nixon et al [24] , Shureiqi et al [25] and Wu et al [26] ( fig. 2 ), makes us believe that the overall effect of 15-LOX-1 and its 13-S-HODE metabolite is largely anti-carcinogenic in colorectal cancer.…”
Section: Is 15-lox-1 Pro-or Anti-carcinogenic? Weighing the Evidencesmentioning
confidence: 95%
See 3 more Smart Citations